Experimental investigation of jet fragment diameter in BWR complicated structures using image processing techniques. Issue 12 (2nd December 2019) - Narushima, Yuki; Saito, Shimpei; Yoshida, Hiroyuki; Abe, Yutaka
ABSTRACT: To estimate the status of the Fukushima Daiichi nuclear power plant's reactor pressure vessel, it is important to understand the breakup and fragmentation behavior of a molten jet of core fuel in the lower plenum of a boiling water reactor (BWR). To clarify the effects of complicated structures on jet breakup and fragmentation, we conducted experiments to visualize jet falling behavior, simulating conditions of a severe BWR accident using a multi-channel experimental apparatus. In this study, we developed a new image-processing method that could recognize fragments in a liquid-liquid flow and estimate fragment diameter of a molten jet in the BWR lower plenum under several inlet conditions. We clarified that complicated structures, such as control rod guide tubes, have little effect on fragment diameter, and that inlet velocity is the dominant factor affecting fragment diameter. This indicates that shear stress would occur at the crest of interfacial waves at the side of the jet, leading to its fragmentation. Finally, the fragment diameters measured in this study show good agreement with the correlation based on shear stress, and a new correlation to predict the jet fragment diameter was developed by fitting the constant correlation value from the experimental result using a simulant fluid.